Analysis of Figurative Language in Short Story “The Bet” a Work by Anton Chekhov 1889 - Syam, Dewi Fatikah; Dahniar, Dahniar (ASHLITION : Ash-Shahabah English Literature, Linguistics, & Education, 2024)
This research aims to figure out the types of figurative language used in the short story “The Bet” by Anton Chekhov and also to figure out the meaning of the figurative language used in the short story “The Bet” by Anton Chekov. The research method used is descriptive-qualitative. To obtain data, the research was conducted by reading the entire short story “The Bet,"analyzing each sentence of figurative language and the meaning of figurative language in the short story. The results showed 10 types of figurative language contained in this short story, namely simile 6 data, personification 2 data, metaphor 3 data, allusion 2 data, irony 3 data, metonymy 2 data, parallelism 1 data, synecdoche 1 data, onomatopoeia 1 data, and symbol 3 data. Of the 10 types of figurative language, simile dominates. The results of the analysis of the meaning of figurative language in this short story show 7 meanings as follows: conceptual 5 data, connotative 9 data, reflective 2 data, collocative no data, social 1 data, affective 5 data, and thematic 2 data. Of these 7 meanings, connotative meaning is the most dominating meaning.